2019
DOI: 10.1080/01634372.2019.1686097
|View full text |Cite
|
Sign up to set email alerts
|

Turning Doctoral Students into Faculty in Gerontological Social Work: The AGESWExperience

Abstract: Developing faculty interested in aging may help social work meet the needs of our growing aging population. However, doctoral students need a variety of supports to complete PhDs and become gerontological social work faculty. This study explored one program's role in supporting the development of social work doctoral students to faculty in gerontology. An email invitation was sent to all former participants (2010-2016 cohorts) of the Association for Gerontology Education in Social Work (AGESW) Pre-Dissertation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In the PDFP network analysis, we evaluated the types and size of professional networks reported by members of the 2010-2012 PDFP cohorts. This approach held the promise to expand on the findings from our previous study (Kusmaul et al, 2019) to delineate specific types of ties (i.e., relational cognitions associated with the level of comfort within a social tie and relational events such as communication and collaborations). The results of the PDFP social network analysis presented below provide an example of the types of findings an egocentric social network analysis can produce.…”
Section: Results Of the Pdfp Social Network Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In the PDFP network analysis, we evaluated the types and size of professional networks reported by members of the 2010-2012 PDFP cohorts. This approach held the promise to expand on the findings from our previous study (Kusmaul et al, 2019) to delineate specific types of ties (i.e., relational cognitions associated with the level of comfort within a social tie and relational events such as communication and collaborations). The results of the PDFP social network analysis presented below provide an example of the types of findings an egocentric social network analysis can produce.…”
Section: Results Of the Pdfp Social Network Analysismentioning
confidence: 99%
“…As we and others (Carman & Fredericks, 2018) have experienced, social network analysis is a powerful yet challenging methodology. In related evaluations of the PDFP, alumni reported that the program contributed to the development of their professional networks (Gibson et al, 2019;Kusmaul et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations